Trafficking In Persons, Especially Trafficking In Women As Prostitutes - Hasudungan Sinaga (Publikasi Indonesia, 2023)
Trafficking in persons, particularly trafficking in women for prostitution, is a troubling crime that violates human rights. This paper aims to delve deeper into the phenomenon of trafficking women for prostitution, the factors influencing this practice, and the efforts that have been made to address this problem. The research method is comprehensive and descriptive, involving literature studies, accurate case analysis, and interviews with various related parties. The results of this study are expected to provide a more complete picture of the problem of trafficking women for prostitution, as well as develop more effective recommendations in the fight against this cruel practice and protect vulnerable victims. Through deeper understanding, it is hoped that concrete action can be taken to end trafficking in persons and restore the dignity of victims caught in this cruel trap.